Forest bioenergy feedstock in Lithuania – Renewable energy goals and the use of forest resources. (April 2019) - Pang, X.; Trubins, R.; Lekavicius, V.; Galinis, A.; Mozgeris, G.; Kulbokas, G.; Mörtberg, U.
Abstract: Demands on forest bioenergy feedstock are expected to increase in many countries due to climate change mitigation. However, sustainable use of forest biomass resources can be ensured only if local and landscape conditions are taken into account, linking energy use to its resource base. The aim of this study was to analyse the forest biomass potential for Lithuania's energy pathways, while comparing the projected demand of forest bioenergy feedstock with resource projections. This was performed using the Landscape simulation and Ecological Assessment (LEcA) tool and the energy model MESSAGE. Biomass demand can be met up to 2050, after which demands under a Biomass Low pathway can still be met by the domestic forest resource if other wood uses are reduced, while Biomass High leads to a biomass deficit regarding domestic forest resources. Information exchange between the energy model and the LEcA tool enables an integrated sustainability assessment, and may contribute to a sustainable and efficient use of forest as a bioenergy feedstock resource. Highlights: The LEcA tool simulates forest growth and management and assesses the resource use Energy pathways for Lithuania were analysed and compared with forest biomass supply Projected use could be met with the Biomass Low pathway, however uncertain after 2050 The Biomass High pathway would lead to a shortage of forest biomass after 2050 Linking the energy model and LEcA tool enabled integrated sustainability assessment